Verifying the resonance schemes of unstable particles at lepton colliders - Shao-Feng Ge; Ui Min; Zhuoni Qian (Physics Letters B)
We propose practical ways of differentiating the various (Breit-Wigner, theoretical, and energy-dependent) resonance schemes of unstable particles at lepton colliders. First, the energy-dependent scheme can be distinguished from the other two by fitting the Z lineshape scan and forward-backward asymmetries at LEP and future lepton colliders with the Z mass mZ, decay width ΓZ, and coupling strength as fitting parameters. Although the Breit-Wigner and theoretical schemes work equally well, the scheme conversion requires the decay width ΓZ to scale inversely with mZ rather than the usual linear dependence from theoretical calculation. These contradicting behaviors can be used to distinguish the Breit-Wigner and theoretical schemes by the precision Z measurements with single parameter (mZ) fit at future lepton colliders. For the WW threshold scan, its combination with the precise Fermi constant provides another way of distinguishing the Breit-Wigner and theoretical schemes.